Performance of Electrochemical Cell to Produce Acid and Alkali for nCaCO(3) Production Using Waste Inorganics - Iqbal, Muhammad Ibrahim; Abbas, Syed Asad; Mehmood, Asad; Kim, Seong-Hoon; Ha, Heung Yong; Jung, Kwang-Deog (ELECTROCHEMICAL SOC INC, 2017)
If an electrolysis system can produce both HCl for Ca extraction and NaOH for carbonation with low energy consumption, mineralization of waste inorganics becomes an economically feasible approach to mitigate environmental CO2 emissions. For this purpose, NaCl electrolysis system with three compartments was fabricated: 1) an anode compartment for hydrogen oxidation, 2) a cathode compartment for hydrogen evolution, and (3) a central compartment between the anionic and cationic exchange membrane where the NaCl solution is introduced. Both 1 M NaOH and HCl were successfully co-produced with a caustic efficiency of 83.6% in the three-compartment cell from a 25 wt% NaCl solution at 1.5 V. Under those conditions, the equilibrium cell potential was 0.83 V. The current density under the optimized operating conditions was 40 mA cm(geo)(-2), and the overpotentials of the cathode (1.0 mg Pt cm(-2)) and anode (0.2 mg Pt cm(-2)) were 0.09 V and 0.05 V, respectively. (c) 2017 The Electrochemical Society. All rights reserved.